130k views
2 votes
Solve itSolve it

Solve it
Solve it
Solve it
Solve it
Solve it
Solve it
Solve it
Solve it
Solve it
Solve it
Solve it

Solve itSolve it Solve it Solve it Solve it Solve it Solve it Solve it Solve it Solve-example-1
User GeertPt
by
5.3k points

2 Answers

4 votes

Answer:

(0,0)

Explanation:

y = 0

2x + 3y = 5x - y Substitute 0 for y

2x + 3(0) = 5x - 0

3x = 5x Subtract 3x from both sides

3x -3x = 5x - 3x

0 = 2x Divide both sides by 2

0 = x

Check

2(0) + 3(0) = 5(0) - 0

0 = 0

User Lschuetze
by
5.1k points
1 vote

Answer:

(0,0)

Explanation:

2x + 3y = 5x - y

First, solve for x.

Subtract 2x from both sides.

3y = 5x - 2x - y

3y = 3x - y

Subtract y from both sides.

3y - y = 3x

2y = 3x

Divide both sides by 2.

y = 1.5x

A solution to the equation is given as,

( x , 0 ) ⇒ ( x , y )

Now substitute y with 0 and find the value of x.

0 = 1.5x

divide both sides by 0.

0 = x

User Kjellski
by
4.9k points